Wychodząc poza życie : Upamiętnianie Holocaustu w poezji Anny Frajlich .......... 149 - Carls, Alice-Catherine (Tu jestem / zamieszkuję własne życie : studia i szkice o twórczości Anny Frajlich, 2018)
LIFE TRANSCENDED: HOLOCAUST MEMORIALIZATION IN THE POETRY OF ANNA FRAJLICHPoetic memorialization internalizes and unites public memorials, personal feelings, and memory. Through iconic images, poetry travels from the general to the particular and from the visible to the invisible; its evocative and integrative powers transcend other memorialization discourses. The poetry of Anna Frajlich, a Holocaust child survivor, exemplifies this type of memorialization. Experiencing the Holocaust through her own and her parents’ exile, she uses their private, daily memorializations as postmemory items, as well as her own experience of post-1938 exile from Poland, to journey back to Holocaust spaces. She reveals the Holocaust as discreet watermarks in her work. Her poetry paints a broad historical perspective covering the entire history and suffering of the people of Israel. It also carries an unconditional affirmation of life, an undying song of beauty. Thus poised between death and life, her poetry demonstrates the healing and transformative power of poetic memorials.